Optimal partition layout of a muffler for thermal energy harvesting and noise attenuation - Oh, Kee Seung; Lee, Jin Woo (INTER-NOISE 2018 - 47th International Congress and Exposition on Noise Control Engineering: Impact of Noise Control Engineering, 2018)
In this study, we present a multi-physics-based topology optimization problem to optimize the inside layout of a muffler for thermal energy harvesting and noise attenuation. Acoustic and thermal analyses are carried out by using the finite element method for non-isothermal acoustic wave and flow. The magnitude of the acoustic pressure at the outlet is minimized, the temperature at the thermal energy spot is maximized, and the pressure drop of a muffler is constrained to create a flow path. A design variable is assigned to each finite element in a design domain, and it varies continuously between 0 and 1. The material properties of each finite element in a design domain are determined by the interpolation function, which is parameterized by the design variable. When one design variable converges to 1, the associated finite element is filled with steel. The finite elements filled with steel build up partitions, which are also thermal conductors, for noise reduction. In contrast, finite elements are filled with air for the design variables of 0. The interpolation functions for acoustic, thermal, and fluidic materials are carefully selected. The formulated topology optimization problem is solved using a gradient-based optimizer for a given design condition.
Keywords: Acoustic pressures; Design condition; Design variables; Gradient based; Interpolation function; Noise attenuation; Optimal partitions; Thermal conductors